Hypothyroidism in Patients with Hepatitis C Infection Visiting a Tertiary Care Hospital (Medical Forum Monthly, 2022)
Objective: The goal of this study is to assess the prevalence of hypothyroidism among hepatitis C patients, presenting to a tertiary care center.Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Liaquat University of Medical & Health Sciences, Jamshoro between January 2022 and June 2022.Materials and Methods: All patients who were aged between 18 and 65 years, irrespective of gender, who had been diagnosed with hepatitis C infection for more than 6 months and did not take any treatment for thyroid dysfunction were included in the study. Patients who were already diagnosed with thyroid diseases before the hepatitis C infection and were on treatment for thyroid dysfunction or underwent surgery or radiation were excluded from the study. All the information was collected on a prescribed proforma.Results: A total of 151 patients were included in the study. A mean age of 45.7 ± 13.4 was observed, and a mean duration of 6.4 ± 3.8 months of hepatitis C infection was noted. A total of 37 out of 151 patients (24.5%) had hypothyroidism in our study. It was found that age between 18-40 years correlated substantially with a higher prevalence of hypothyroidism.Conclusion: The study concluded that hypothyroidism was documented in a large number of patients presenting with hepatitis C infection.